The Role and Contribution of Prof. Imam Suprayogo in the Development of Islamic Education in Indonesia - Risal Apriono; Rustam Ibrahim (al-Afkar, Journal For Islamic Studies, 2025)
This research examines Prof. Imam Suprayogo, a key figure in the development of Islamic education in Indonesia. Through his integrative educational concept, he not only streamlined the curriculum at UIN Malang but also played a role in shaping the thinking and direction of Islamic education development nationally in Indonesia. His progressive thinking on the integration of science and religion has shaped the profile of Islamic education that is relevant to current developments, without separating Islamic teachings from education and without losing its Islamic essence. His role in this concept serves as an example for future generations in continuing the vision of modern and meaningful Islamic education and realizing a generation of faith and piety.